T-shirt quilts made easy - DeLeonardis, Martha (American Quilter's Society, 2012)
"T-shirt quilts are easy to make. Martha has mastered the art of stabilizing fabrics to make the quilt top into straight lines. She then uses a 'Comparative Quilt Design Chart' to show how to arrange blocks of various sizes into a visually pleasing whole. Use Martha's finished quilts as jumping-off points to design your own quilt"--Provided by publisher.